The effect of methionine to cysteine substitution on the stability of formate dehydrogenase from Candida methylica - Ordu, Emel B.; Yelboga, Emrah; Secundo, Francesco; Sessions, Richard B.; Karaguler, Nevin Gul (ELSEVIER SCIENCE BV, 2012)
Because of its industrial importance. the FDH enzyme has been subjected to several protein engineering studies in order to stabilise it at high temperatures. In this study, methionine to cysteine substitution (M1C) and disulphide bridge formation between residues 1 (M1C) and 62 (D62C) were investigated in terms of their effect on the thermostability of cmFDH. Although the mutant cmFDHs, D62C and M1C/D62C, did not show the improvement expected in its stability, characterisation studies of individual mutants showed that the M1 residue is related to temperature stability. Catalytic efficiency (k(cat)/K-m) of the M1C single mutant was 63% better than that of the native cmFDH and the T-m value of this mutant was measured as significantly higher than that of the native cmFDH by using fluorescence measurements and Circular Dichroism Spectra. Comparing to other studies related to Cys or Met substitution in the literature, 2 degrees C enhancement of T-m, is a promising result for the industrially important FDH enzyme and to understand the relationship between thermostability and Met to Cys substitution. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Candida methylica; Disulphide bridge; Enzyme activity; Methionine substitution; Protein stability; THERMAL-STABILITY; RESIDUES; MUTAGENESIS; RESISTANCE; BOIDINII; Biochemistry & Molecular Biology; Chemistry